Does foreign aid act as an instrument of economic growth in India and Sri Lanka? - Sethi, Narayan; Bhujabal, Padmaja; Sahoo, Malayaranjan; Sucharita, Sanhita (Penerbit Universiti Kebangsaan Malaysia, 2019)
Foreign aid is considered as an important instrument of the foreign policy of states. It acts as a major source of foreign exchange earnings for developing countries. Therefore, it is regarded as a basic pillar of developmental process. We examine the trends and composition of foreign aid inflows in India and Sri Lanka. This study also empirically examines the relationship between foreign aid or Overseas Development Assistance (ODA) and economic growth for India and Sri Lanka using the annual data 1960-1961 to 2014-2015. Further, this study aims to test the causal relationship among foreign aid with other macroeconomic variables such as domestic investment, financial sector development and trade, and inflation rate of these countries. We have employed Johansen and Juselius (JJ) (Johansen and Juselius, 1990) procedure of testing for the presence of multiple cointegrating vectors. We have also used Vector Error Correction (VECM)-Granger Causality test to find out the short run dynamic equilibrium relationship among the variables. The empirical results show that there are both short and long run equilibrium relationships existing between foreign aid and economic growth with other macroeconomic variables in both the countries. However, the direction of inter-linkage between foreign aid and economic growth contradicts to each other in case of India and Sri Lanka, both in short run and long run. We have found that the error correction term is positive and significant in selected macroeconomic variables indicating a long-run causality in India and Sri Lanka.